OPTIMALISASI TUGAS PERAWATAN KESEHATAN OLEH KELUARGA SEBAGAI UPAYA MENINGKATKAN STATUS KESEHATAN PENDERITA HIPERTENSI DI KELURAHAN SIMPANG TIGA SIPIN KECAMATAN KOTABARU TAHUN 2019 - Netha Damayantie (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2019)
Hypertension is one very serious disease and generally sufferers do not know it has hypertension before checking blood pressure. When hypertension is not treated, it can result in more effects such as heart disease, myocardial infarction, stroke, or renal failure, which ends with death. Early detection and effective hypertension treatment can prevent increased blood pressure and complications. Hypertension control can be done through a family approach. Community service aims to optimize health care tasks by the family as an effort to improve the health status of people with hypertension in Kelurahan Simpang Tiga Sipin Kecamatan Kotabaru 2019. Activities consist of preparation stage, implementation and evaluation. The form of activity is health screening and health education activities involving lecturers and students in nursing department with participants from 56 people. Expected increased family knowledge after counseling. Health counseling through information communication about the optimization of family tasks by using audio visual further strengthens the understanding of the family. Puskesmas Paal V can follow up on results with family approach. Make the family of hypertension patients as assisted families, in collaboration with health promotion programs to conduct education and programs of untransmitted diseases for the control of blood pressure and regular treatment of patients with hypertension.